Cyclic stretch induced oxidative stress by mitochondrial and NADPH oxidase in retinal pigment epithelial cells - Liang, Xida (BMC Ophthalmol, 2019)
BACKGROUND: Vitreomacular adhesion (VMA) has been reported to associated with age-related macular degeneration (AMD). Understanding the mechanisms underlying cyclic stretch induced in retinal pigment epithelial cells (RPE) may be important for the treatment of VMA-related AMD. METHOD: Cyclic stretch (1HZ, 20% elongation) was applied to cultured ARPE-19 cells for 15 min, 2 h, 6 h, 12 h, 24 h by flexcell FX-5000 Tension system. Total reactive oxygen species (ROS) were detected using DCFH-DA. Mitochondrial superoxide were detected using MitoSOX Red mitochondrial superoxide indicator. NADPH oxidases (NOX) and signaling pathways, such as p38 and PKC, were detected using western blot. Apocycin (Apo) were used as NOX inhibitors. RESULT: High levels of total ROS were detected from 15 min to 24 h, whereas mitochondrial superoxide were higher only in early time. NOX2 were significantly increased at 24 h. NOX4 were significantly increased at 2 h and reach its peak at 24 h. P-p38 was significantly increased at 12 h and 24 h. P-PKC was significantly increased at 15 min and kept a persistent high level. The upregulated expression of NOX4 by cyclic stretch can be significantly decreased under p-PKC inhibitor other than p-p38 inhibitor. CONCLUSION: Cyclic stretch induce oxidative stress from both mitochodrial and NADPH oxidase in RPE cells, which may prompt oxidative damage in VMA-related AMD.